ANALISIS HUBUNGAN KEBIJAKAN MONETER DENGAN INFLASI DI INDONESIA - Nova Nova (Fakultas Ekonomi Universitas Almuslim Bireuen, 2022)
This research aims to examine the relationship between monetary policy and inflation in Indonesia. The research method uses quantitative descriptive. The analysis model used is a vector autoregressive model. The research results show that the money supply has no long-term effect on inflation in Indonesia. The exchange rate has a long-term effect on inflation in Indonesia. Interest rates have no long-term effect on inflation in Indonesia.